Maternal empowerment and healthcare access determines stillbirths and early neonatal mortality in Pakistan: analysis of demographic and health survey 2012-13 - Jamil Ahmed; Ashraful Alam; Camille Raynes-Greenow (Inishmore Laser Scientific Publishing Ltd, 2018)
# Background To determine how a lack of women's empowerment affects their risk of stillbirths and early neonatal mortality in Pakistan. # Methods Pakistan Demographic and Health Survey 2011-12 data were used to analyse 11,985 and 11,596 singleton births in the 5 years preceding the survey, respectively, for stillbirth and early neonatal mortality. Multivariate logistic models, adjusted for survey cluster were performed in STATA (Stata Inc, College Station, TX, USA) using step-wise backward elimination to measure associated factors of stillbirth and early neonatal mortality in separate models. Results are presented as adjusted odds ratios (aOR). # Results Women whose family elders made their healthcare decisions compared to women who decided for themselves had higher odds of stillbirth (aOR=2.04, 95% confidence interval (CI)=1.05-3.99). Women who had never used any family planning, compared to modern methods were 1.47 times more likely to have experienced a stillbirth (aOR=1.47, 95% CI=1.06-2.04). Women who did manual labour compared to no work (aOR=1.55, 95% CI=1.09-2.21), or were a blood relation with their husband also had higher odds of stillbirth (aOR=1.45, 95% CI=1.01-2.06). Early neonatal mortality was explained mainly by mothers facing financial problems to access to treatment (aOR=1.67, 95% CI=1.06-2.63), babies not weighed at birth (aOR=4.39, 95% CI=1.00-19.33), malnourished mothers (body mass index BMI \<18.5, aOR=1.61, 95% CI=1.00-2.58) and mothers who wanted their last child later than when they were born (aOR=0.17, 95% CI=0.05-0.59). # Conclusions Women's empowerment to choose and access healthcare for themselves and their newborns during pregnancy and birth should be the cornerstone of any intervention package to tackle stillbirths and early neonatal mortality in a high burden country like Pakistan.